Jordan generalized Γ- (σ,τ) -Derivation on Prime Γ-Near Rings - Kadhim, Ali Kareem (Iraqi Journal of Science, 2022)
In this paper, we introduce the notion of Jordan generalized Derivation on prime and then some related concepts are discussed. We also verify that every Jordan generalized Derivation is generalized Derivation when  is a 2-torsionfree prime .